Fast operation of active mirrors on synchrotron beamlines - Sutter, John P.; Alcock, Simon G.; Foster, Andrew; Khosroabadi, Hossein; Axford, Danny; Owen, Robin; Fernandes, Daniel; Sawhney, Kawal (Journal of physics. Conference series, 2025)
The Optics & Metrology group at Diamond Light Source has recently published a description of a bimorph deformable X-ray mirror operating in closed-loop using multi-beam interferometric feedback. This “adaptive” mirror can make fast and stabilised changes to the X-ray beam profile. Beam shaping at a rate of 1 Hz was achieved, a contrast to the now usual “set and forget” operation of “active” bimorph mirrors at synchrotrons. However, this breakthrough cannot be applied to synchrotron beamlines without a robust control system that allows the mirror to be rapidly and controllably deformed. Diamond has now responded to this need by taking an integrated approach, considering: the bimorph power supplies, the beamline control software, the beam imaging camera, the bimorph mirror optimisation software, and the bimorph mirror itself as part of a single system. In collaboration with CINEL, new HV-ADAPTOS high-voltage power supplies have been made available. The latest models contain new firmware that adds features not previously available, such as piezo-elastic creep compensation. Communication with the HV-ADAPTOS power supplies over Ethernet has been made more reliable by a new EPICS asynPortDriver interface developed at Diamond and rolled out to all appropriate Diamond beamlines. A new Bluesky/Ophyd plan for the measurement of the bimorph mirror’s piezo response functions is under development and has undergone its preliminary tests. This plan is expected to be less affected by upgrades of the beamline control software than previous solutions. It relies on beam images produced by Gigabit Ethernet cameras and processed by the EPICS areaDetector driver. Finally, the need for strain-free clamping of the mirror has now been fully recognized and procedures for ensuring it have been put into practice. Although such a system is more complex than that required for a mechanically bent mirror, it gives bimorph mirrors an ability to operate rapidly and repeatably that other optics do not offer, and it lays a foundation for more advanced beam-shaping functions.